PROFESIONALISME AUDITOR DAN TINGKAT MATREALITAS DALAM MENENTUKAN KETEPATAN PEMBERIAN OPINI PADA KANTOR AKUNTAN PUBLIK (KAP) DI BANDUNG - Sakti Muda Nasution (LPPM POLITEKNIK LP3I BANDUNG, 2016)
ABSTRACT : The growth of business world in Indonesia time to time felt progressively competitive. Every company has an effort to survived in business competition. Company management need the service of third party to have the financial statement accountable to outside party and can improve the management company credibility, such as auditor external. Target of this Research is to know the applying of professionalism of auditors and materiality level at Public Accountant in Bandung, and to know the influence of professionalism of auditors and materiality level to accuracy of opinion at Public Accountant firms in Bandung simultaneously and partially.In SPAP SA Seksi 200 PSA No. 04 ( 2001) expressing that